The Philosopher’s Poet: Twenty-First-Century Perspectives on Wallace Stevens - Bart Eeckhout (Transatlantica)
This article investigates how the relation between poetry and philosophy is developed in a sample of reflections on the philosophical qualities of the American Modernist poet Wallace Stevens’s work. It offers a critical presentation of a handful of twenty-first-century published responses to Stevens’s poetry emanating from two different quarters: fellow poets and philosophers. The five selected poets (David Baker, Linda Gregerson, Carl Phillips, Stanley Plumly, and Carol Frost) collectively pondered Stevens’s philosophical qualities in a recent issue of the New England Review, while the responses by philosophers Alain Badiou and Peter Hare were published in collections of their essays. The two different angles are investigated precisely because they fall outside mainstream literary criticism on Stevens and help to dramatize several of the difficulties confronted by poets and philosophers seeking to find common ground. By pitting the voices of poets against those of philosophers, the article allows the reader to observe empirically how poets are often wary of addressing Stevens’s philosophical weight except by noting the formal and stylistic enactment of mental activity in his verse, while philosophers sometimes fail to acknowledge the intrinsic nature of lyric thinking, and thus do not always manage to contribute to a deeper understanding of the poetry as such.